FILARET KOLESSA: THE FOUNDER OF UKRAINIAN ETHNOGRAPHIC MUSEUMOLOGY AND HIS CONTRIBUTION TO THE PRESERVATION OF THE NATIONAL CULTURAL HERITAGE - Данилевич, Аліса (ВПЦ "Київський університет", 2025)
The purpose of the study is to conduct a comprehensive study of the scientific activity of Filaret Kolessa as the founder of Ukrainian ethnographic museology and to analyze his contribution to the preservation of the national cultural heritage. Research methodology. The research used general scientific methods (generalization, comparison, induction and deduction), applied the historical-biographical method to analyze the life path of Filaret Kolessa, as well as empirical-theoretical methods (analysis, synthesis) to systematize the scientific works of Filaret Kolessa, content analysis for studying scientific texts, and source analysis for archival materials research. Results. The results of the study showed that Filaret Kolessa played a key role in the formation of Ukrainian ethnographic museology. It has been established that his scientific expeditions and research into folk music contributed to the preservation and popularization of the rich cultural heritage of the Ukrainian people. It was found that F. Kolessa developed methods of collecting, systematizing and analyzing ethnographic materials, which became the basis for the further development of Ukrainian ethnomusicology. It was established that the works of F. Koless had a significant impact on the formation of national identity and the preservation of cultural heritage, especially in the context of researching the musical traditions of Lemkivshchyna, Boykivshchyna and Transcarpathia for the collection of folklore material. It is worth noting that thanks to the activities of F. Koless, a significant number of Ukrainian folk songs were collected and published, which have been preserved in the archives and continue to be studied by modern scientists. Based on the analysis, it can be stated that F. Kolessa's contribution to the creation and development of museums and archives with ethnographic materials is important for the cultural heritage of Ukraine, which confirms his status as the founder of Ukrainian ethnographic museology. Conclusions. As a result of the conducted research, we can note that Filaret Kolessa played a central role in the formation of Ukrainian ethnographic museology and preservation of the national cultural heritage. It was established that the activity included not only the systematization and preservation of Ukrainian folklore, but also the active implementation of scientific approaches to ethnographic research, which became the basis for the development of modern museology in Ukraine.

Мета дослідження – провести всебічне дослідження наукової діяльності Філарета Колесси як основоположника українського етнографічного музеєзнавства та проаналізувати його внесок у збереження національної культурної спадщини. Методологія дослідження. У дослідженні було використано загальнонаукові (узагальнення, порівняння, індукція і дедукція), застосовано історико-біографічний метод для аналізу життєвого шляху Філарета Колесси, а також емпірико-теоретичні методи (аналіз, синтез) для систематизації наукових праць Філарета Колесси, контент-аналіз для вивчення наукових текстів, та джерелознавчий аналіз для дослідження архівних матеріалів. Результати дослідження показали, що Філарет Колесса відіграв ключову роль у становленні українського етнографічного музеєзнавства. Встановлено, що його наукові експедиції та дослідження народної музичної творчості сприяли збереженню і популяризації багатого культурного спадку українського народу. Зʼясовано, що Ф. Колесса розробив методи збору, систематизації та аналізу етнографічних матеріалів, що стали основою для подальшого розвитку української етномузикології. Встановлено, що роботи Ф. Колесса мали значний вплив на формування національної ідентичності та збереження культурної спадщини, особливо в контексті дослідження музичних традицій Лемківщини, Бойківщини та Закарпаття для збору фольклорного матеріалу. Варто відзначити, що завдяки діяльності Ф. Колесса, було зібрано та опубліковано значну кількість українських народних пісень, що збереглися в архівах і продовжують досліджуватися сучасними науковцями. На основі проведеного аналізу можна констатувати, що внесок Ф. Колесси в створення та розвиток музеїв і архівів з етнографічними матеріалами є важливим для культурної спадщини України, що підтверджує його статус як основоположника українського етнографічного музеєзнавства. Висновки. В результаті проведеного дослідження, можемо відзначити, що Філарет Колесса відіграв центральну роль у формуванні українського етнографічного музеєзнавства та збереженні національної культурної спадщини. Встановлено, що діяльність включала не лише систематизацію та збереження українського фольклору, але й активне впровадження наукових підходів до етнографічних досліджень, що стало основою для розвитку сучасного музеєзнавства в Україні.
ФІЛАРЕТ КОЛЕССА: ОСНОВОПОЛОЖНИК УКРАЇНСЬКОГО ЕТНОГРАФІЧНОГО МУЗЕЄЗНАВСТВА ТА ЙОГО ВНЕСОК У ЗБЕРЕЖЕННЯ НАЦІОНАЛЬНОЇ КУЛЬТУРНОЇ СПАДЩИНИ
Keywords: Filaret Kolessa; Ukrainian ethnographic museology; national cultural heritage; history of Ukraine; Філарет Колесса; українське етнографічне музеєзнавство; національна культурна спадщина; історія України